Banana Production and Productivity Enhancement through Spatial, Water and Nutrient Management - M M Mustaffa (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2012)
Bananas and plantains globally the fourth important food crop, recorded wide variation in production and productivity in most of the banana growing regions. This is attributed mainly to the variety, type of planting material used, season and method of planting besides management techniques such as water and nutrients. Among all the commercial varieties of banana, owing to comparatively higher yield potential and better marketability both in domestic and export markets the Cavendish group of bananas such as Grand Naine, Williams, Robusta are preferred over other cultivars of banana. Planting sword suckers is beneficial and more ideal conventional planting material than the water suckers, butts and bits of rhizomes. However, the in-vitro banana plants of Dwarf Cavendish and Robusta are superior to conventional suckers due to their vigorous growth, early flowering (19 days) and reduced crop duration by 29 and 22 days, respectively. With reference to plant spacing and planting density which is determined by varieties grown, soil fertility status, prevailing climatic conditions etc. and maintenance of lower density of 625-1000 plants ha-1 recorded low productivity at <30t ha-1, while, high density of 5000 plants ha-1 recorded 120t ha-1. However, time taken for maturity was distinctly longer in higher densities, with 120 and 160 days Bunch grade and fruit quality are, however determined by pre-harvest bunch management practices. Influence of method of irrigation, fertilizer application and the role of nutrient elements, organic farming, INM and use of bunch sleeves on yield and fruit quality in different commercial cultivars under various conditions is discussed.